Raw Materials, Profits, and the Productivity Slowdown: Some Doubts - Grubb, David (Quarterly Journal of Economics, 1986)
Journal Article Raw Materials, Profits, and the Productivity Slowdown: Some Doubts Get access David Grubb David Grubb London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 101, Issue 1, February 1986, Pages 175–184, https://doi.org/10.2307/1884647 Published: 01 February 1986